Dispute settlement reports 2019. Volume X, Pages 5225-5634 - World Trade Organization (Cambridge : Cambridge University Press, 2021)
These are the WTO's authorized and paginated reports in English. They are an essential addition to the library of all practising trade lawyers and a useful tool for students and academics worldwide working in the field of international economic or trade law. DSR 2019: Volume X contains the panel and Appellate Body reports on 'Ukraine - Anti-Dumping Measures on Ammonium Nitrate' (WT/DS493).
Title from publisher's bibliographic system (viewed on 09 Apr 2021).
Keywords: Foreign trade regulation -- Cases; Tariff -- Law and legislation -- Cases; Competition, Unfair -- Cases; Dispute resolution (Law) -- Cases